Електронна черга громадян як елемент електронного урядування - Романів, Тетяна; Марковець, Олександр (Видавництво Львівської політехніки, 2018)
The article describes the introduction of e-government in Ukraine and its impact on the development of the information society. The importance of electronic service at the present stage of electronic government of Ukraine is presented. The advantages and disadvantages of the electronic queue are determined.
Keywords: інформаційні технології; електронний уряд; електронний сервіс; послуги; електронна черга